2018
DOI: 10.1029/2018gl077966
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Mud‐Induced Periodic Stratification in a Hyperturbid Estuary

Abstract: This study presents new observations of fluid mud transport and of the interaction between mud‐induced stratification and the flow. Data collected in a hyperturbid estuarine tidal channel reveal details of the intratidal entrainment asymmetry, characterized by quasi‐instantaneous entrainment and upstream pumping of mud during flood, and a gradual reduction of layer thickness by shear dispersion during ebb. Rapid restratification early during the flood phase restores the predominant two‐layer structure and deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…These results capture the qualitative characteristics of the observed ETM; observations made by Talke, De Swart, and Schuttelaars () during one cruise in 2006 show sediment concentrations near the bed of 10–30 kg/m 3 and near the surface of approximately 1 kg/m 3 in the entire zone between km 35 and 60. Similar or higher near‐bed concentrations and fluid mud have been observed by Wang (), Papenmeier et al (), Winterwerp et al (), and Becker et al (). De Jonge et al () reports observed surface concentrations locally exceeding 3 kg/m 3 .…”
Section: Model Calibration and Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…These results capture the qualitative characteristics of the observed ETM; observations made by Talke, De Swart, and Schuttelaars () during one cruise in 2006 show sediment concentrations near the bed of 10–30 kg/m 3 and near the surface of approximately 1 kg/m 3 in the entire zone between km 35 and 60. Similar or higher near‐bed concentrations and fluid mud have been observed by Wang (), Papenmeier et al (), Winterwerp et al (), and Becker et al (). De Jonge et al () reports observed surface concentrations locally exceeding 3 kg/m 3 .…”
Section: Model Calibration and Resultssupporting
confidence: 84%
“…Once the transition to high sediment concentrations has occurred, the model lacks several physical processes that are essential to describe the sediment dynamics. This shows in the 2005 model results by an overestimation of the M 4 tidal water level amplitude and insufficient vertical structure to capture the observed distinct fluid mud layers (e.g., Becker et al, ). Furthermore, while lower sediment concentrations are observed during periods of high discharges (Winterwerp et al, ), the strong flushing found in the model for discharges higher than 70 m 3 /s does not correspond to the observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The velocities were measured with a Flowquest 600 kHz acoustic Doppler current profiler (ADCP) sampling at 0.5 Hz and recording an average over 60 s to remove high‐frequency variability, with a vertical bin size of 0.5 m. Velocity data within the near‐bed region (~0.07 H , where H is the water depth, Nystrom et al, 2007) are affected by sidelobe interference and are not used in further analysis. Although 600 kHz ADCP has been confirmed valid in current measurements in high SSC environments (Becker et al, 2018), the ADCP velocity records can be biased by spikes due to high SSC (Cao et al, 2012), which is the case in this study. Hence, a 11‐min moving average filter was applied to the ADCP velocity profiles to remove the spikes, similar to that of Becker et al (2018).…”
Section: Methodsmentioning
confidence: 54%